STRATEGI DALAM PENGEMBANGAN UMKM WARUNG SEMBAKO MURAH DI JALAN TUAMANG - Zainarti Zainarti; Dea Amanda Putri; Dede Endrico; Naia fingkani solin (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The aim of this research is to find a strategy for developing Cheap Grocery Stall MSMEs on Jalan Tuamang, Medan City, which is effective in increasing sales and business sustainability. Thus, it is hoped that this research can contribute to the development of MSMEs in Indonesia. This research uses a qualitative method with a descriptive analytical approach at the Cheap Grocery Stall on Jalan Tuamang, Medan City, there are several data collection and analysis techniques used to dig up in-depth information. This research shows that the Cheap Grocery Stall on Jalan Tuamang has succeeded in developing a mature strategy to face challenges and take advantage of opportunities in operating its business. One of the main findings of this research is the use of effective marketing strategies, such as promotion via social media and word of mouth marketing, which successfully attracts customer attention. Apart from that, this shop maintains price competitiveness while maintaining a reasonable profit margin.